Studies in Medievalism XX : Defining Neomedievalism(s) II. - Fugelso, Karl (Studies in medievalism., 2011)
Following on from previous issues, this volume continues to explore definitions of neomedievalism and its relationship to traditional medievalism. In four essays that open the volume, Harry Brown, KellyAnn Fitzpatrick, David W. Marshall, and Nils Holger Petersen underscore the elusive nature of distinctions between the two fields, particularly when assessing contemporary film, music, and electronic media. Seven articles then test the need for these distinctions, on subject matter ranging from Sir Walter Scott as a historian; M.E. Braddon's gendered medievalism; friendship models in Mary Eliza.